EFFECTS OF DIFFERENT WEEDING TIME OF RYEGRASS ON GROWTH AND YIELD COMPONENTS OF WHEAT (Triticum spp.) IN JIMMA ARE, SOUTH WEST ETHIOPIA - Terefe, Haile; Denberu, Ewnetu; Woldesenbet, Abebe (International Journal of Research -GRANTHAALAYAH, 2016)
The experiment was conducted at Jimma University College of Agricultures and Veterinary Medicine (JUCAVM) under field condition to determine the effects of different weeding time of Ryegrass on growth and yield components of Wheat (Triticum spp.) The experimental design used was randomized complete block design (RCBD) and each of the experimental treatment was replicated three times. A Wheat cultivar, Digalu was grown with Ryegrass and different weeding time of Ryegrass T1 (weeding 15-45 DAS), T2 (weeding 30-60 DAS), T3 (weeding 45-75 DAS), T4 (weed free) and T5 (no weeding) were used as a treatment. Data were recorded on Wheat Plant height, Stem thickness, Number of tillers; Spike length and Spike number. The result revealed that various weeding time of Ryegrass statistically (p≤0.05) affected Plant height, Stem thickness, Number of tillers; Spike length and Spike number. The maximum values of all the parameters were recorded in the (15-45 DAS) except for Plant height and Stem thickness. Whereas, the minimum values of these parameters were recorded from (45-75 DAS) except for Plant height. It is advisable for growers to remove the Ryegrass before the critical weed-crop competition period which is most probably (15-45 DAS) to keep the crop weed free at this period.